The gospel of kindness animal welfare and the making of modern America - Davis, Janet M. (Oxford University Press, 2016)
"When we consider modern American animal advocacy, we often think of veganism, no-kill shelters, Internet campaigns against trophy hunting, or celebrities declaring that they would "rather go naked" than wear fur. Contemporary critics readily dismiss animal protectionism as a modern secular movement that privileges animals over people. Yet the movement's roots are deeply tied to the nation's history of religious revivalism and social reform. The Gospel of Kindness explores the broad cultural and social influence of the American animal welfare movement at home and overseas from the Second Great Awakening to the Second World War. Dedicated primarily to laboring animals at its inception in an animal-powered world, the movement eventually included virtually all areas of human and animal interaction.
Includes index
Keywords: Geschichte 1790-1945; HISTORY / United States / General; NATURE / Animal Rights; Geschichte; Animal welfare -- United States -- History; Animal rights -- United States -- History; Social values -- United States -- History; Tierrecht; Tierschutz; USA; United States -- Social conditions; United States -- History